Heller myotomy versus endoscopic balloon dilatation for achalasia: a single center experience - Nickel, Felix; Benner, Laura; Rupp, Christian; Müller, Philip C.; Müller, Beat P.; Linke, Georg R. (Medicine, 2019)
This study aimed to compare clinical results, symptom relief, quality of life and patient satisfaction after the 2 most common procedures for achalasia treatment: laparoscopic Heller myotomy (LHM) and endoscopic balloon dilatation (EBD). - Patients treated at University Hospital of Heidelberg with LHM or EBD were included. A retrospective chart review of perioperative data and a prospective follow-up of therapeutic efficiency, Gastrointestinal Quality of Life Index (GIQLI) and patient satisfaction was conducted. - Follow-up data (mean follow-up: 75.1 ± 53.9 months for LHM group and 78.9 ± 45.6 months for EBD) were obtained from 36 patients (19 LHM; 17 EBD). Eckardt score (median (q1,q3): 2 (1,4) in both groups, P = .91, GIQLI (LHM: 117 (91.5, 126) vs EBD: 120 (116, 128), P = .495) and patient satisfaction (3 (2,3) vs 3 (2,4), P = .883) did not differ between groups. Fifteen patients (78.9%) in LHM group and 11 (64.7%) in EBD group (P = .562) stated they would undergo the intervention again. All patients with EBD had at least 2 dilatations (100%), whilst only 2 patients (10.5%) had dilatation after LHM (P < .001). There were no complications after EBD, but 2 after LHM (10.5%, P = .517). - Both LHM and EBD are able to control symptoms and provide similar quality of life and patient satisfaction. However, reintervention rate was higher following EBD, hence LHM provided a more sustained treatment than EBD.
Gesehen am 06.02.2020